Comparing the groundwater quality of region 10 of Tehran to the Iranian and EPA drinking water standards - Fatemeh Effati; Javad Bayat; Maryam Rouhi Kerigh; Masoume Mollaei (علوم محیطی)
Introduction: In recent years, urban development, population growth, and increasing human activities created many problems in the aquatic resources in urban areas. Awareness of the quality of water has great importance due to the increasing need for drinking water in the metropolitan cities. In this study water quality variables were examined to determine the quality of grounwater and the risk of toxic and conventional pollutants in terms of human consumption. Material and methods: For this purpose, a number of nine wells were selected to investigate the groundwater quality in ward 10 of the municipality of Tehran in the years 2014 and 2016, in the summer and winter. The physical variables including temperature, color, turbidity, and salinity and chemical variables including dissolved oxygen (DO), pH, electrical conductivity (EC), total suspended solids (TSS), total dissolved solids (TDS), nitrite (NO2-), nitrate (NO3-), ammonium (NH4+), total phosphorus (TP), total nitrogen (TN), sodium (Na), calcium (Ca), magnesium (Mg), copper (Cu), iron (Fe), lead (Pb), cobalt (Co), zinc (Zn), and detergent as well as microbial variables were measured. Results and discussion: The results showed that due to the presence of coliform bacteria and high levels of NO3-, the groundwater was polluted by human or animal wastewaters, but there was no serious problem, and it was possible to improve the water quality by processes such as chlorine disinfection. Among the physical variables, only the turbidity was almost twice the standard level in some wells. The Analyses of heavy metals showed that the concentrations of Pb, Zn, Fe, and Cu in the groundwater were extremely high, being several times higher than the reported standard level. Changes in TP were very high and reported up to 0.21 mg. Although total coliform and fecal coliform were low, they violated the EPA standard for drinking water. The presence of these two variables in the groundwater is an indication of the penetration of human or animal wastes into the groundwater and, if used, it will cause harmful effects on the health of at-risk people. The total hardness also did not have many fluctuations with a maximum value of 390 mg, which seems fairly favorable, since a concentration of 300 mg is optimal for this variable, and 600 mg is the maximum total hardness of drinking water. The interpolation maps of the groundwater quality index indicated that in the summer of 2014, most of the districts were considered to be in bad and medium conditions, but in the winter of the same year, the conditions changed to medium and relatively good. The water quality index for toxic pollutants in the mentioned seasons and years was in good and very good levels, indicating the groundwater was not polluted by the toxic variables used to determine the index. Conclusion: The reported data for physiochemical and microbial variables showed that the groundwater in the study area had not serious problems, and only the water turbidity exceeded the standard level. Using chlorine disinfection processes to eliminate coliform bacteria and treatments to reduce water turbidity seem to improve water quality. The calculated groundwater indices for the district water indicated that most of the ward, in terms of conventional pollutants, was in the bad-to-medium category in 2014, while in 2016, the quality category changed to medium to fairly good.